Konseling Indigenous Pesantren (Gaya Kepimpinan Kyai dalam Mendidik Santri) - Khiyarusoleh, Ujang (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study aims to find the surrounding indigenous pesantren through the kyai leadership style in educating students. The method used is a systematic review through review articles using inclusion criteria and exclusion criteria. Article searches were accessed from internet searches in the database, namely: proquest.com, Scincedirect and google scholar with the keywords leadership style, Kyai leadership, and santri education. Data analysis was done by collecting articles that met the inclusion criteria collected and examined systematically. Search for literature published from 2015 to 2020. The results of the study showed that the kyai’s leadership style in educating students was a leader who had unique characteristics and became an example for his students and had a duty to carry out the task of developing this nation and country. The figure of a kyai who was sincere, simple and tenacious in educating and disciplined in carrying out his duties, this was all reflected in the characteristics of a teacher in Islam, namely, as Murabbi, Muallim, Muaddib and Mudaris. Therefore, the kyai is an exemplary and charismatic figure who is able to influence both within the pesantren and outside the pesantren or in society, so that the students will be similar to the leader of the pesantren, namely the kyai when they have graduated.